2022
DOI: 10.1177/10406387221139799
|View full text |Cite
|
Sign up to set email alerts
|

A series of heterogeneous lymphoproliferative diseases with CD3 and MUM1 co-expressed in cats and dogs

Abstract: Lymphoma diagnosis in dogs and cats is continually evolving as new subtypes and human correlates are being recognized. In humans, T-cell lymphomas with MUM1 expressed and plasma cell neoplasia or B-cell lymphomas with CD3 expressed aberrantly are reported only rarely. We report here a case series of tumors in dogs and cats with CD3 and MUM1 co-expressed as determined by immunocytochemistry or immunohistochemistry. Lineage was assigned for these tumors by 3 board-certified pathologists and a veterinary immunolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…MUM1/IRF4 expression is also well documented in multiple dendritic cell subsets in people and mice 7,8 . Though it is widely used as a plasma cell marker in veterinary immunohistochemical and immunocytochemical panels, recent reports in veterinary literature also describe MUM1 immunoreactivity in canine cutaneous histiocytomas, 2 and in some canine T‐cell lymphomas 9 . This case both highlights the imperfect specificity of this marker for plasma cells and corroborates the potential for MUM1 immunoreactivity of Langerhans histiocytes as documented by Stillwell et al in canine cutaneous histiocytomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MUM1/IRF4 expression is also well documented in multiple dendritic cell subsets in people and mice 7,8 . Though it is widely used as a plasma cell marker in veterinary immunohistochemical and immunocytochemical panels, recent reports in veterinary literature also describe MUM1 immunoreactivity in canine cutaneous histiocytomas, 2 and in some canine T‐cell lymphomas 9 . This case both highlights the imperfect specificity of this marker for plasma cells and corroborates the potential for MUM1 immunoreactivity of Langerhans histiocytes as documented by Stillwell et al in canine cutaneous histiocytomas.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Though it is widely used as a plasma cell marker in veterinary immunohistochemical and immunocytochemical panels, recent reports in veterinary literature also describe MUM1 immunoreactivity in canine cutaneous histiocytomas, 2 and in some canine T-cell lymphomas. 9 This case both highlights the imperfect specificity of this Langerhans cell precursors. 10 BRAF V600E mutation is one such mutation that is identified in 30-40% of human LCH cases and has been suggested as a prognostic factor for high-risk disease in people.…”
mentioning
confidence: 99%
“…Lymphoma cells that co-express T and B cell antigens have been reported in humans, dogs, cats, and birds in the genera Amazona sp. and cockatiel [ 7 , 14 , 22 , 29 , 38 , 41 , 43 , 44 , 45 , 57 , 58 , 60 ]. However, the possibility of unexplained nonspecific binding of anti-CD20 and anti-BLA36 antibodies to the T cell area cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…One study found the most frequent site of origin to be the skin [ 5 ], whilst other reports suggested oral plasmacytomas are the most common [ 1 , 2 , 3 ]. The incidence of plasmacytomas in cats is much lower, and the literature mostly consists of case reports of a single animal [ 7 , 8 , 9 , 10 , 11 ], although there are some studies with larger sample numbers ( n = 7–11) [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%